STUDY OF THE EXISTING SYSTEM OF EQUITY CONSTRUCTION INVOLVING INDIVIDUALS INVESTMENT IN REАL ESTАTE AND ITS DEVELOPMENT PROSPECTS - V. A. Opekunov; M. D. Allahverdova (Вестник университета)
The article considers the problems of attracting funds from private investors by the developer of residential real estate. Problems of realization of the under-construction residential real estate in accordance with the Federal Law on Share Participation have been investigated. Characteristic aspects of realization of residential real estate at the time of construction have been determined. The dynamics and structure of changes in the system of share participation have been reviewed, and also the perspectives of its development and changes have been defined and analyzed, with the indication of the influence of these changes on the residential real estate market.